A Note on the Physical and Mechanical Properties of Canarium strictum Roxb. (Dhuna) from Assam - Sekhar, A. C.; Singh, K. R. (Indian Forester, 1978)
Physical and Mechanical properties have been evaluated and reported in green, air-dry and kilu-dry conditions based on small clear specimens obtained from ten logs from ten different naturally grown trees of Canarium strictum. Roxb. (Lhuna) received from Margherita Range Digboi Division, Assam in thid paper. The results have been compared with standard teak in green, air-dry and kilu-dry conditions calculated values based on strength specific gravity formulae have also been reported for comparison.